EVALUATION OF ACCELERATION OF ATMOSPHERIC ELECTRONS DUE TO HIGH POWER HF TRANSMISSION TO EARTH IONOSPHERE - Martin,I.M. (Universidad de Tarapacá. Facultad de Ingeniería, 2006)
It should be possible, for countries in the southern hemisphere, to develop a joint scientific program aimed at studying the properties and behavior of the Earth's ionosphere, based on terrestrial HF power transmitted radiation. The goal of this work is to further acquire knowledge about the physical and electrical properties of the Earth's ionosphere (plasma), which are of particular importance, since they can affect communication and navigation systems and climate changes. Required research instruments for the southern hemisphere measurements and also plasma calculations for Antarctica (EACF) are described. The main facilities research apparatus consists of a high power HF transmitter that can be used to temporarily excite a limited area of the Earth's ionosphere for scientific studies. The question addressed in this work is: What is the maximum energy attained by ionosphere electrons accelerated by electromagnetic wave radiation from a ground based high power HF transmitter?